Studies on bacterial respiratory pathogens causing bacteraemia and meningitis in South Africa - Gottberg, Anna Margareta, von (My University, 2014)
Introduction Analysis of surveillance data on bacterial respiratory pathogens most commonly causing bacteraemia and meningitis may be useful to measure the impact of vaccination, monitor antimicrobial resistance emergence and document changes in disease epidemiology. Materials and methods Active, laboratory-based, national surveillance for invasive Haemophilus influenzae, meningococcal and pneumococcal disease in South Africa was conducted. Isolates, cultured from normally sterile sites, were submitted for phenotypic and genotypic characterisation. Trends are described and univariate and multivariable models were used to assess differences among groups. Results Following the introduction of H. influenzae serotype b conjugate vaccine (HibCV) in 1999, the number of Hib cases reported for infants <1 year decreased by 65%, from 55 cases in 1999-2000 to 19 cases in 2003-2004. Despite high HibCV coverage, rates of Hib disease in children <5 years then increased from 0.7 per 100,000 population in 2003 to 1.3/100,000 in 2009. Among 263 Hib episodes, 135 (51%) were classified as vaccine failures and 53% of these occurred among children who were not HIV infected. An investigation of meningococcal disease in Gauteng, revealed rates of disease which increased from 0.8/100,000 in 2000 to 4.0/100,000 in 2005; the percentage due to serogroup W135 increased during this time from 7% (4/54) of cases to 75% (221/295). Overall case-fatality ratios doubled from 11% in 2003 to 22% in 2005. Our investigations revealed that the expansion of the Hajj clone explained the emergence of serogroup W135 during this time, as 95% of W135 isolates (285/301) were identified as one clone by pulsed-field gel electrophoresis and seven representative strains belonged to the ST-11/ET-37 complex. Among invasive pneumococcal disease (IPD) cases, 12 levofloxacin-non-susceptible pneumococci were identified in children <15 years, and were found to be associated with a history of tuberculosis (TB) treatment and nosocomial IPD in two treatment centres for multidrug-resistant TB (MDR TB). From 2003 through 2008, prior to pneumococcal conjugate vaccine (PCV) introduction, among IPD cases in children <5 years, 58% (3849/6668), 65% (4314/6668), and 85% (5669/6668) of cases and 61% (455/751), 64% (482/751), 82% (616/751) of deaths were due to serotypes included in 7-valent PCV (PCV-7), PCV-10 and PCV-13, respectively. PCV-13 had significantly higher coverage for isolates from blood culture than for isolates from cerebrospinal fluid: 3882/4531 (86%) vs. 1670/2009 (83%), p=0.009, but only differed by 3%. An analysis of risk factors revealed the relative risk of IPD was 21-fold (95% CI, 19–24) and 34-fold (29–41) greater in HIV-infected compared to HIV-uninfected children in the <1 year and 1–4-year-old age groups, respectively. Discussion and conclusions After initial reductions in Hib disease, vaccine failures, occurring in both HIV-infected and -uninfected children, comprised half of the rise in Hib disease detected 10 years after national introduction of Hib vaccine, given as three doses without a booster. These data contributed to the decision to add a booster dose of Hib vaccine in South Africa in 2009. Continued surveillance of meningococcal serogroup W135 revealed evidence that this serogroup had become endemic in Gauteng causing more severe disease than the previous predominant serogroup A strain. Paediatric fluoroquinolone use for MDR TB led to the emergence and nosocomial spread of levofloxacin-non-susceptible pneumococci. Existing pneumococcal vaccine formulations have the potential to prevent most cases and deaths from IPD among HIV-infected and -uninfected children in South Africa. Surveillance of pneumococcal meningitis may provide representative data for monitoring the impact of PCV.
Keywords: Bacteremia; Meningitis; Bacterial Infections